Protocol Followed for Management of Hypernatremia in a White–tailed Deer Fawn (Odocoileus virginianus) - Rosenhagen, Nichole; Whittington, Julia (Wildlife Rehabilitation Bulletin, 2014)
A white‒tailed deer fawn with suspected trauma presented to a wildlife medical facility in central Illinois. Initial triage revealed clinical signs highly indicative of head trauma and shock, including ataxia, disorientation, and tachycardia. The fawn was administered subcutaneous isotonic fluids and oral meloxicam. The following day, hematologic evaluation revealed profound hypernatremia and azotemia. Meloxicam was discontinued and treatment with slow intravenous administration of 5 percent dextrose in water (D5W) was initiated to correct the hypovolemia and hypernatremia. Within three days, the fawn was able to suckle and ambulate normally. Chemistry values returned to normal within one week of admission. Electrolyte disturbances are common in orphaned neonatal animals suffering from starvation, dehydration, and shock, and inappropriate fluid therapy in the face of these disturbances may further compromise an animal’s condition. Thus, the fluid composition, rate, and route of administration are critical for care of these patients.